Russian Federation Financial Sector Assessment Program : Financial Infrastructure Technical Note - World Bank (World Bank, Washington, DC, 2016)
Financial infrastructure is the underlying foundation of a country’s financial system. It comprises all institutions, the rules, and standards of all the systems which enable financial intermediation. The quality of a country’s financial infrastructure determines the efficiency of intermediation, the ability of lenders to evaluate risk and of borrowers to obtain credit, insurance, and other financial products at competitive terms. For instance, the efficient and smooth functioning of the payment, and securities settlement systems facilitates the discharge of financial obligations and the safe transfer of funds across distances and institutions and retail customers, supporting the stability of the financial system. This technical note contains the assessment of the national payment and settlement systems (NPS) infrastructure in Russia using the framework of international standards6 and the experience and previous work of the World Bank on payment systems development7 in several countries around the world. The assessment was undertaken in the context of the IMF and World Bank (WB) joint Financial Sector Assessment Program (FSAP) mission to Russia during March 15-30, 2016. The assessor was Gynedi Srinivas of the World Bank’s Payment Systems Development Group. The assessor will like to thank the counterparts in Russia for their excellent cooperation and hospitality during the mission. The technical note assesses the NPS infrastructure in Russia under four broad themes. These are: (i) Legal and regulatory framework; (ii) Payment system landscape; (iii) Systems for post-trade clearing and settlement - Central Securities Depository and settlement depository and Central counterparty; and (iv) Oversight. It does not provide a detailed assessment of individual payment and settlement systems in the form of a Report on Observance of Standards and Codes (ROSC).